Hollywood's road to riches - Waterman, David, 1947- (Harvard University Press, 2005)
Combining historical and economic analysis, this book shows how, beginning in the 1950s, a largely predictable business has been transformed into a volatile and complex multimedia enterprise now commanding over 80 percent of the world's film business. At the same time, the book asks how the economic forces leading to this success--the forces of audience demand, technology, and high risk--have combined to change the kinds of movies Hollywood produces.